2020
DOI: 10.3390/agronomy10030323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Greenhouse CO2 Supplementation on Yield and Mineral Element Concentrations of Leafy Greens Grown Using Nutrient Film Technique

Abstract: Carbon dioxide (CO2) concentration is reported to be the most important climate variable in greenhouse production with its effect on plant photosynthetic assimilation. A greenhouse study was conducted using a nutrient film technique (NFT) system to quantify the effect of two different levels of CO2 (supplemented at an average of 800 ppm and ambient at ~410 ppm) on growth and nutritional quality of basil (Ocimum basilicum L.) ‘Cardinal’, lettuce (Lactuca sativa L.) ‘Auvona’, and Swiss chard (Beta vulgaris L.) ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It is important to note that the alteration of basil leaf pigments due to chilling stress could damage the photosynthetic apparatus, with detrimental impacts on plant growth and development. Previous studies have revealed that basil's greenness is an indicator of chlorophyll content, usually used by consumers to determine its productivity [19]. Therefore, further research is required to quantify basil's physiological response to low-temperature stress to promote the breeding of cold-tolerant genotypes of basil.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the alteration of basil leaf pigments due to chilling stress could damage the photosynthetic apparatus, with detrimental impacts on plant growth and development. Previous studies have revealed that basil's greenness is an indicator of chlorophyll content, usually used by consumers to determine its productivity [19]. Therefore, further research is required to quantify basil's physiological response to low-temperature stress to promote the breeding of cold-tolerant genotypes of basil.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the concentration of carbon dioxide (CO 2 ) is another microclimatic variable that directly affects the photosynthetic assimilation of plants and, therefore, is a variable that must be monitored inside greenhouses [ 49 ]. In the case of this study, it should be mentioned that the greenhouses studied do not have carbon enrichment systems, and there is no local information on the behavior of this variable in these types of greenhouses.…”
Section: Resultsmentioning
confidence: 99%
“…This can be explained in two ways: promoting photosynthesis and increasing water use efficiency. This is because separately supplying carbon dioxide in agricultural facilities or plant factories plays a significant role in increasing production [34].…”
Section: Discussionmentioning
confidence: 99%